Defining post-operative pancreatitis as a new pancreatic specific complication following pancreatic resection. Issue 8 (August 2016) - Connor, Saxon
Abstract: Introduction: Post-operative pancreatic fistula has been well defined. However the underlying aetiology remains poorly understood. The aim of this review was to investigate whether the underlying aetiology for a proportion of patients suffering from post-operative pancreatic fistula was due to post-operative pancreatitis. Method: A systematic literature review according to the PRISMA guidelines. The date range was from 2005 to 2016. The search strategy included the terms: post-operative pancreatitis, pathophysiology, post-operative pancreatic fistula, pancreaticoduodenectomy, ischaemic pancreatitis, microcirculation and pancreatitis, serum and drain amylase and lipase. The data was summarised without quantitative or qualitative analysis. Results: There exists significant physiological, biochemical, clinical and histological evidence in the literature that a proportion of post-operative pancreatic fistula is due to post-operative pancreatitis. A new definition of post-operative pancreatitis based on the presence of biochemical evidence for pancreatic inflammation (urinary trypsinogen-2 >50 ug/L or serum amylase/lipase > upper limit of normal) between post-operative days 0–2. Predicted severity is based on C-reactive protein with a cut-off of 180 mg/L at post-operative day 2. The proposed grading of severity is in line with previous work by international study group of pancreatic surgery. Conclusion: Post-operative pancreatitis should be recognised as a separate pancreatic specific complication following pancreatic resection. Improved recognition may allow better understanding of potential methods of prevention, treatment and prediction of severity.